SOME ASPECTS OF USING BIOTIN-CONTAINING PREPARATIONS IN VARIOUS HAIR LOSS CONDITIONS (International Scientific Journal Alfraganus, 2025)
The article discusses the use of biotin-containing preparations in the treatment of different types of hair loss. Biotin, also known as vitamin B7 or vitamin H, plays an important role in maintaining healthy hair, skin, and nails. This review examines clinical studies demonstrating the effectiveness of biotin in improving hair condition and reducing hair loss. It also considers the mechanisms of biotin action on hair follicles and its influence on hair growth processes. In addition, recommendations on dosage and duration of use, as well as possible side effects and contraindications, are discussed. The review provides useful information for physicians and patients interested in effective prevention and treatment of hair loss.
Keywords: biotin; hair loss; vitamin B7; hair follicle; dermatology